The acoustic characterization of green materials. Issue 2 (June 2017) - Iannace, Gino
Natural materials are a valid alternative to traditional synthetic materials in the fields of acoustic treatments and energy saving. Natural fibres have been used to produce sound-absorbing panels. This article reports the acoustical characterization of the following natural fibres: straw, hay, plant litter and different sized wood chips. The acoustic measurements were carried out with an impedance tube. The acoustic absorption values were measured in a frequency range between 200 and 2000 Hz.